Comparing Machinability Performance of TISIN Coated HSS Tool with Uncoated HSS Tool for CNC Green Machining (CNC Turning) of High Strength Steel Alloy (EN9) for Improving Machining Rate and Surface Finish (Journal of Pharmaceutical Negative Results, 2022)
Aim: The objective of this paper is to minimize surface roughness and increase material removal rate (MRR) in cnc green machining of Novel Titanium Silicon Nitride (TISIN) coated High Speed Steel (HSS) tool with uncoated High Speed Steel (HSS) tool for cnc green machining (cnc turning) of high strength steel alloy (en9). Materials and Methods: The machining performance of high strength steel alloy material is compared with the novel Novel Titanium Silicon Nitride (TISIN) coated High Speed Steel Tool and Uncoated High Speed Steel (HSS) tool. Sample size calculated with the settings of Gpower 80%. Total number of groups is 2 and the sample size is 16 per group. Hence total samples involved are 32. Results: The results revealed that the average material removal rate improved from 57015.09mm3/min to 9209.18 mm3/min by use of the noval Titanium Silicon Nitride coated High Speed Steel Tool instead of conventional uncoated tool. Similarly the surface roughness reduced from 1.805125 µm to 0.458 µm. The Significance of P value obtained was 0.012 (p<0.05) for material removal rate and p=0.04 (p<0.05) for surface roughness observations. Conclusion: Within the limitations of the studies, the performance of high strength steel alloy with Noval Titanium Silicon Nitride coated High Speed Steel Tool recorded a higher material removal rate (14.89%) than the conventional High Speed Steel Tool. Similarly, the proposed coated tool reduced surface roughness 59.43% than the conventional uncoated tool.